Energy economics science, policy, and economic applications - Sadler, Thomas R. (Lexington Books, 2020)
Energy Economics: Science, Policy, and Economic Applications explains various energy systems from an economics perspective. Specifically, the author uses the tools of economics to analyze the development of modern energy systems, the world's reliance on fossil fuels, and the components of a transition to cleaner energy resources.